2022
DOI: 10.21203/rs.3.rs-1344848/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metapangenomics reveals an increased proportion of an Escherichia coli-dominated enterotype in older Chinese people

Abstract: Background:Gut microbial communities are likely remodeled along with accumulated physiological decline during aging. Here, we performed a metagenomics-based enterotype analysis in a geographically homogeneous cohort of 367 enrolled Chinese individuals between the ages of 60 and 94, with the goal of characterizing the gut microbiome of the older Chinese individuals and identifying factors linked to enterotype variations.Results:In addition to two adult-like enterotypes were dominated by Bacteroides spp. (ET-Bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…Investigations into the oral microbiome demonstrated that different oral habitats are associated with specific functions, such as oxaloacetate decarboxylase metabolism in a tongue-enriched subgroup of H. parainfluenzae [28]. In humans, meta-pangenomics of Escherichia in older Chinese individuals highlighted higher abundance in the gut microbiome, with implications for dietary habits and gut health during aging [29]. The meta-pangenomics give us new insights into bacteria genome in its host and/or environmental metagenomes and its microbial functions related to host physiology and habitat preferences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations into the oral microbiome demonstrated that different oral habitats are associated with specific functions, such as oxaloacetate decarboxylase metabolism in a tongue-enriched subgroup of H. parainfluenzae [28]. In humans, meta-pangenomics of Escherichia in older Chinese individuals highlighted higher abundance in the gut microbiome, with implications for dietary habits and gut health during aging [29]. The meta-pangenomics give us new insights into bacteria genome in its host and/or environmental metagenomes and its microbial functions related to host physiology and habitat preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-pangenomics is a novel approach combining pangenomes and metagenomes to investigate bacterial genomes recruited reads in their environmental metagenomes, providing broader perspectives of understanding the roles of its distribution and biogeographical patterns through the microbial population [27,28]. Meta-pangenomics have been applied to investigate the human microbiome, revealing the distribution of identical genes in pangenomes across populations in different locations and ages [28,29]. The adaptation of microbial populations in extreme environment from deep sea microbiome also has been investigated by metapangenomics [30,31].…”
Section: Introductionmentioning
confidence: 99%